Numerical experiments for radial dynamics and opacity effect in argon plasma focus - Ali, Z.; Ali, J.; Saw, S. H.; Lee, S. (2012)
A z-pinch in its simplest form is a column of plasma in which current (J) is driven in the axial direction (z) by an electric power source producing an azimuthal (θ) direction magnetic field (B) that tends to confine plasma by (J × B) force. One application of this configuration is Plasma Focus. Dense plasma focus (DPF) is essentially a pulsed electric gas discharge between coaxially arranged electrodes. DPF devices belong to the family of dynamic Z-pinches which are self-constricted plasma configurations. The Lee model code was developed to simulate the plasma dynamics in a DPF. The model incorporates the energy and mass balances equivalent, at least in the gross sense, with radiation-coupled dynamics to all the processes which are not even specifically modeled. It is a well known fact that radiation loss is an inevitable phenomenon in the final stage of pinch compression. The most obvious one is that of a focus or a Z-pinch. Plasma self-absorption is an important factor during the pinch compression. In this paper the effect of self absorption of line radiation was investigated in argon plasma by a series of numerical experiment considering both aspects, i.e., by including and excluding the self absorption term in Lee code. The results were compared for various parameters, i.e., Radial trajectories, pinch duration, pinch current, line radiation yield while changing pressure. The effect of radiation self absorption was observed in last few fractions of seconds (200–300 ns). Considering self absorption, the compression shows a value of radius of about 0.2 mm while a collapse (radiative collapse) was observed otherwise. The results illustrated that the radiation cooling becomes significant when the plasma is dense and turn to be opaque for radiation. Hence in real case we do not see a radiative collapse in argon PF as self absorption plays in real experiments. The results of pinch duration and pinch current also indicated that self absorption is essentially enhancing the pinch in terms of stability.